Comparative analysis of national strategies for safety and health at work - Lissner, Lothar; Reihlen, Antonia; Höcker, Herrad; Elo-Schäfer, Johanna; Stautz, Andreas (Dortmund, 2010)
"In this study strategic concepts and methods in the area of occupational safety and health (OSH strategies) have been analysed for selected countries. Beyond that the transferability of such concepts and methods to the German system has been examined. The intent was to determine the main features of the various strategies, to evaluate their respective strengths and weaknesses and to identify their essential differences and similarities. "